Beneath the city's grid: vernacular and (post-)colonial planning interactions in Dakar, Senegal. (January 2018) - Bigon, Liora; Hart, Thomas
Abstract: Research on the urban grid plan in colonial contexts tends to analyse the grid as an occidental top-down phenomenon that was inscribed on a spatial tabula rasa of indigenous environments overseas. Moreover, after the implementation of the grid plan, urban planning historiography treats the colonial city a Western creation almost exclusively, and is quiet about the variegated vernacular responses to this urban form. This article contributes to the shifting of this historiographic balance. Rich in visual evidence, primary sources and observations in situ, it brings to the fore a dynamic tapestry of challenging interactions between endogamous and exogamous planning cultures in an African city – interactions that are all but unidirectional in character. Against the background of the French colonial grid plan design of Dakar, the vernacular Lebou traditions of settlement configuration are discussed. The article demonstrates that the indigenous and colonial planning cultures became intimately entangled and hybridised, changing their character across time, moving from attempts of erasure to competition and creative cohabitation. It reveals that ancient spatial practices have remarkably still survived in Dakar's very city centre – a gridded area that since its creation has been considered in both academic and popular discourses as the most Western site in West Africa. Highlights: Demonstrates that endogamous and exogamous urban planning traditions have continuously interacted in Senegal. This interaction informs research on grid plan designs by considering cities in the global South. Explores the variegated vernacular responses to the Western originated grid plan in Dakar. Demonstrates the incorporation of the pénc (or public square), a pre-colonial spatial design, into the modern grid plan. Shows that grid-pénc relations in Dakar have persisted over a long period, even in the most Westernised city centre.